Advances and challenges in grid tied photovoltaic systems - Mirhassani, S.; Ong, Hwai Chyuan; Chong, W.T.; Leong, K.Y. (Elsevier, 2015)
Photovoltaic (PV) technology is gathering momentum around the word. Global PV energy harvest has been more than doubled since 2010. Grid connected PV (GCPV) systems can be found in different scales classified into three categories of small scale, medium scale and utility scale. Considering size of the system various configurations are suggested for the GCPV systems while each configuration might be assessed by factors such as efficiency, reliability, expandability and cost. Moreover, high integration of GCPV systems into the power system network creates several technical problems mostly coming from the intermittent nature of solar energy. In addition, to achieve a higher degree of power system reliability, GCPV systems are required to support the grid in abnormal condition such a faults and deviation from standard frequency. This paper provides a comprehensive review on GCPV systems. Various configuration proposed by the literature will be discussed. Cost study and impact of technical and environmental factors on the total expense and revenue of GCPV installation will be investigated. Different aspects of PV integration into the power network will be discussed. Problem and solutions will be studied as well. Finally grid requirements and active and reactive power support will be reviewed. (C) 2015 Elsevier Ltd. All rights reserved.